Responses of several measures to different intensity levels of upper limb exergames in children with neurological diagnoses: a pilot study - Goikoetxea-Sotelo, Gaizka; van Hedel, Hubertus J. A. (Frontiers in Rehabilitation Sciences, 2024)
BackgroundTherapy intensity is among the most critical factors influencing neurorehabilitative outcomes. Because of its simplicity, time spent in therapy is the most commonly used measure of therapy intensity. However, time spent in therapy is only a vague estimate of how hard a patient works during therapy. Several measures have been proposed to better capture the amount of work a patient puts forth during therapy. Still, it has never been analyzed how these measures respond to changes in therapist-selected exercise intensity in children with neurological conditions.ObjectivesTo investigate the response and the reliability of heart rate variability (HRV), skin conductance (SC), activity counts per minute (AC/min), movement repetitions per minute (MOV/min), and perceived exertion to different therapist-tailored intensity levels of upper limb technology-assisted therapy in children with neurological conditions.MethodsIn this pilot cross-sectional study, participants engaged in three personalized, randomized exergame intensity levels (“very easy”, “challenging”, “very difficult”) for eight minutes each. We assessed all measures at each intensity level. The experiment was conducted twice on two consecutive days. We quantified reliability using intra-class correlation coefficients (ICC).ResultsWe included 12 children and adolescents aged 11.92 (±3.03) years. HRV, MOV/min, and perceived exertion could differentiate among the three intensity levels. HRV, MOV/min, perceived exertion, and AC/min showed moderate to excellent (0.62 ≤ ICC ≤ 0.98) test-retest reliability.ConclusionHRV, MOV/min, and perceived exertion show potential for becoming valid and reliable intensity measures for an upper limb robotic rehabilitative setting. However, studies with larger sample sizes and more standardized approaches are needed to understand these measures’ responses better.